Synergistic effect of biological activated carbon and enhanced coagulation in secondary wastewater effluent treatment - Aryal, Ashok; Sathasivan, Arumugam; Vigneswaran, S. (International Association on Water Quality, 2012)
The use of secondary wastewater effluent (SWWE) is an essential strategy for making better use of limited water resources. However, a wide range of organic compounds eventually renders them unsuitable for recycling. In water treatment processes, biologically activated carbon (BAC) is adopted after physicochemical treatment. However, the effectiveness of such combination for SWWE remains poorly understood. This study investigates the effectiveness of various combinations: BAC/enhanced coagulation (EC) or EC/BAC, especially in terms of dissolved organic carbon (DOC) removal. The results showed that distinct advantage could be obtained by adopting BAC/EC combination rather than EC/BAC, as microbes in BAC not only remove non-coagulable compounds but also synergize the removal efficiency by releasing some coagulable humic substances.